POST PARS PLANA VITRECTOMY CATARACT SURGERY: SURGICAL OUTCOME - Shahnam, Tariq; Khalil, Muhammad Zia-ud-din; Jan, Sanaullah; Aziz, Abdul (Journal of Postgraduate Medical Institute, 2019)
Objective: To determine surgical outcome after cataract surgery in post pars plana vitrectomised eyes. Methodology: This was an interventional study conducted at Department of Ophthalmology, Khyber Girls Medical College, Hayatabad Medical Complex, Peshawar, from 1st February 2016 to 30th November 2016. A total of 73 eyes of 73 patients who underwent cataract surgery in previously vitrectomised eyes were assessed for surgical outcome. Cataract surgeries were performed by manual small incision cataract surgery (MSICS) or phacoemulsification with intraocular lens (IOL) implantation. Visual acuity was recorded at baseline and at 40th post-operative day. Intraoperative and postoperative complications were documented. For statistical data analysis, snellen's visual acuity was converted to Log MAR. Visual outcome was graded as improvement, stable or deterioration. The data were analyzed using SPSS version 20. Results: The mean age of our patients was 45 ±7 years. Males were 64.4% while 35.6% were females. In our study, 82.19% cases had improvement in visual acuity, 10.96% patients had stable visual acuity and 6.84% had deterioration from baseline visual acuity. The difference between baseline and follow up visual acuity was statistically significant (p =0.045). Most common intraoperative complication was posterior capsular plaque (28.7%) and most common postoperative complication was retinal detachment (13.7%). Conclusion: Cataract surgery improved visual outcome in significant number of eyes that had undergone pars plana vitrectomy despite intraoperative and postoperative challenges.